Feasibility Study to determine if administration of Carbonic anhydrase inhibitor Acetazolamide (Diamox) will cause aquaresis but prevent hyponatriemia in a healthy population: SALT Study. Issue 4 (2018) - Grewal, Gurinder S; , Teri M Kozik; Hickman, Mary C; Connolly, Therese F; Bajwa, Randeep S; Bhattacharyya, Mouchumi
No abstract available